Comprehensive comparison of monotherapies for psychiatric hospitalization risk in bipolar disorders. (19th June 2018) - Nestsiarovich, Anastasiya; Mazurie, Aurélien J; Hurwitz, Nathaniel G; Kerner, Berit; Nelson, Stuart J; Crisanti, Annette S; Tohen, Mauricio; Krall, Ronald L; Perkins, Douglas J; Lambert, Christophe G
Abstract : Objectives: This study compared 29 drugs for risk of psychiatric hospitalization in bipolar disorders, addressing the evidence gap on the >50 drugs used by US patients for treatment. Methods: The Truven Health Analytics MarketScan ® database was used to identify 190 894 individuals with bipolar or schizoaffective disorder who filled a prescription for one of 29 drugs of interest: lithium, first‐ or second‐generation antipsychotics, mood‐stabilizing anticonvulsants, and antidepressants. Competing risks regression survival analysis was used to compare drugs for risk of psychiatric hospitalization, adjusting for patient age, sex, comorbidities, and pretreatment medications. Other competing risks were ending monotherapy and non‐psychiatric hospitalization. Results: Three drugs were associated with significantly lower risk of psychiatric hospitalization than lithium: valproate (relative risk [RR] = 0.80, P  = 3.20 × 10 −4 ), aripiprazole (RR = 0.80, P  = 3.50 × 10 −4 ), and bupropion (RR = 0.80, P  = 2.80 × 10 −4 ). Eight drugs were associated with significantly higher risk of psychiatric hospitalization: haloperidol (RR = 1.57, P  = 9.40 × 10 −4 ), clozapine (RR = 1.52, P  = .017), fluoxetine (RR = 1.17, P  = 3.70 × 10 −3 ), sertraline (RR = 1.17, P  = 3.20 × 10 −3 ), citalopram (RR = 1.14, P  = .013), duloxetine (RR = 1.24, P  = 5.10 × 10 −4 ), venlafaxine (RR = 1.33; P  = 1.00 × 10 −6 ), and ziprasidone (RR = 1.25; P  = 6.20 × 10 −3 ). Conclusions: This largest reported retrospective observational study on bipolar disorders pharmacotherapy to date demonstrates that the majority of patients end monotherapy within 2 months after treatment start. The risk of psychiatric hospitalization varied almost two‐fold across individual medications. The data add to the evidence favoring lithium and mood stabilizer use in short‐term bipolar disorder management. The findings that the dopaminergic drugs aripiprazole and bupropion had better outcomes than other members of their respective classes and that antidepressant outcomes may vary by baseline mood polarity merit further investigation.